Straits settlements Blue Book (imports/exports) 1915-1916 vol.64-66 (Great Britain : Public Record Office, 1971)
Mengandungi'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to and exports of the other countries in 1914 and 1915';'Blue Book for the year 1916';'Straits Settlements return of imports and exports during the year 1916'.